Pressurized CF3I-CO2 Gas Mixture under Lightning Impulse and its Solid By-Products - M. S. Kamarudin; A. Haddad; B. C. Kok; N. A. M. Jamail (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper describes tests results on the CF3I-CO2 gas mixtures as an alternative for SF6 gas as to be used as insulating medium in high voltage applications. Pressurized CF3I-CO2 gas mixtures are subject under standard lightning impulse voltages at both positive and negative polarities. Under rod-plane configuration, the electrode gap length and gas pressure are varied accordingly. Upon completion of the laboratory tests, SEM and EDX analyses are carried out to assess the solid by-products. It was found that higher gas mixtures provide better insulation strength. In terms of weight, 50% of the solid by-product is found to be iodine.